PENGARUH KEPEMIMPINAN, KOMPENSASI DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KOTA PADANG - Yusuf Firmansyah Satriyo; idris idris (Jurnal Riset Manajemen Bisnis dan Publik, 2015)
This study aims to analyze Influence Leadership, Compensation and Organizational Climate on job satisfaction of employees at the Regional Disaster Management Agency (BPBD) Padang. This study uses quantitative methods. The study population was all public servants who work in Padang BPBDs totaling 58 people, and samples were taken with a stratified random sampling with a sample size of 51 people. Data was collected using a questionnaire. The results were analyzed by the method of data collection path analysis (path analysis) using SPSS. The results based pathway analysis showed that (1) the direct effect of leadership variables amounting to 7.39% and the indirect effect of 4.06% on job satisfaction through organizational climate, (2) variable compensation amounted to 10.63% direct effect and influence 3% directly to job satisfaction through organizational climate, (3) the direct effect of organizational climate variables for 25.76% of the employee satisfaction BPBDs Padang, while 49.16 is influenced by other factors outside the study. Keywords: Leadership, Compensation, Organizational Climate and Job Satisfaction